Food safety [videorecording (DVD)] - Locke, Jonathan (Just the facts (Learning Zone Express (Firm)), 2007)
Chef Jonathan Locke discusses how to keep food safe with his extensive knowledge of safe food preparation, food-borne illness, clean-up and storage.